Strategi Peningkatan Loyalitas Pelanggan dan Keberlanjutan Bisnis: Peran Kunci Kepuasan Konsumen dan Faktor Internal-Eksternal Pelanggan Sekolah Kewirausahaan Bina Amanah Cordova – Tangerang - Astarini, Dyah; Risqiani, Renny; Curry, Khirstina; Amalia, Anisah Z; Abnuri, Aslih; Lestari, Desy Sekar (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The training conducted by the Community Service Team (PkM) FEB-Usakti is to provide knowledge and understanding of the Strategy for Increasing Customer Loyalty and Business Sustainability at Bina Amanah Cordova Entrepreneurship School (SKBAC) in Tangerang. The program, attended by 17 entrepreneurs (10 females, 7 males) primarily from the food industry, utilized a methodological framework comprising lectures and interactive discussions. Preceding the main event, preparatory activities included surveys, coordination meetings, module development, and partner liaisons. Held on January 15, 2021, the session engaged participants in a pre-test and post-test to gauge their comprehension. Results indicated an increased understanding among participants regarding the significance of catering to both internal and external consumers and achieving customer satisfaction. These insights are vital for developing strategies aimed at fostering customer loyalty and ensuring sustainable business practices. Participants acknowledged the training as highly beneficial and in alignment with their expectations. It is hoped that future PkM activities will be a continuation of previous activities by providing material that supports this activity so that there is a complete and continuous activity. The output that has been produced in addition to Publication in Accredited Journals is the creation of Intellectual Property Rights in the form of Copyright